Changes in Serum Protein Profile in Laying Hens Housed in a Cage-Free System - Csilla Tóthová; Edina Sesztáková; Blanka Galiková; Veronika Glembová; Veronika Oršuľaková; Oskar Nagy (Veterinary Medicine International)
The objective of this study was to characterize the distribution of serum proteins in laying hens reared under cage-free open farm conditions and to evaluate the changes in the concentrations of serum protein fractions throughout the 1-year laying period. Ten Dekalb White white-egg–laying hens were blood sampled from the wing vein at 17, 22, 29, 38, 50, 60, and 70 weeks of age. Egg laying was observed at 18 weeks of age. The average daily egg production in the initial phase of laying (week 22) was 6.3, reaching the maximum (8.5 eggs) in week 38. After a slight decrease, from week 60, the egg production increased repeatedly and stayed relatively constant till the end of the study (8.1–8.3 eggs). The serum samples were analyzed for the concentrations of total proteins and the electrophoretic pattern of serum proteins. Five protein fractions were identified on the serum protein electrophoretogram of the hens, including albumin, α1-, α2-, β-, and γ-globulins. The size and shape of the fractions differed significantly according to the stage of the laying period. Significant changes were detected in the ratio of all individual protein fractions as well as in the concentrations of total proteins and protein fractions. The concentrations of total proteins, albumin, α2-, β-, and γ-globulins decreased significantly after the beginning of egg production compared to values recorded before laying (p<0.05) and started to increase after reaching the maximum egg production in week 38. The A/G ratios were higher before and at the beginning of the laying period, and the lowest values were obtained in weeks with the highest egg production. These findings suggest that the beginning of egg production is the most critical period in the laying cycle of hens reared under alternative farming conditions characterized by the most marked alterations in the serum protein profile.